Transformation of the image of Japanese Americans in U.S. newspapers: From the raid on Pearl Harbor to the internment act - E. L. Zberovskaya; Zamakhaev V.V. (Японские исследования)
The article is devoted to the transformation of the image of Japanese residents of the United States in the American press after the country’s entry into World War II and before the beginning of their internment. The main sources chosen were the media that influenced the formation of public opinion: the press of the western states, where most Japanese lived, and The New York Times, a national newspaper. The study examined published editorials, speeches by politicians, officials of various ranks, and representatives of public associations and groups. Content analysis of The New York Times publications allowed us to interpret the quantitative characteristics of the articles’ content.